A critical multimodal framework for reading and analyzing pedagogical materials. Issue 1 (8th April 2019) - Huang, Shin-ying
Abstract : Purpose: This paper aims to propose a critical multimodal framework to understanding pedagogical materials that focuses on not only the verbal or the visual components but also the interaction between the two semiotic resources that constructs power relations as a result of intermodal interaction, and it further provides an example of an in-depth analysis of one text using this approach. Design/methodology/approach: The paper proposes a critical multimodal framework that draws fromSerafini (2010 ) and Royce (1998). Details about how the two works complement to form a critical multimodal framework are discussed, after which the paper analyzes one example from an English-language textbook using the proposed framework to demonstrate its strengths. Findings: The findings highlight the power relations constructed in texts as a result of the interaction between the verbal and visual components, specifically how the visual mode functions to rationalize the power relations constructed in the verbal mode. These findings also establish the significance for considering the larger context of materials production and reception identified in the ideological perspective to appreciate how texts reflect discourses in diverse locales. Originality/value: This paper argues that even though critical multimodality has often been discussed conceptually in L1 literacy scholarship, how to put these conceptualizations into practice has not been addressed systematically. The paper also contends that critical perspectives to understanding multimodal texts are also important in L2 English-language teaching. The critical multimodal framework proposed thus serves as a conceptual and methodological framework for multimodal reading and interpretive practices in both L1 and L2 contexts.